A tourism area life cycle model with an index-dependent growth rate for modelling the poststagnation stage - M. Rodrigo; I. Ajala; A. K. Irhanida (Annals of Tourism Research Empirical Insights, 2025)
The resilience of the tourism industry is increasingly reliant on robust health infrastructure and effective disease detection systems, particularly in the face of ongoing global health challenges. This study introduces a modified tourism area life cycle model to explore the interplay between health preparedness and tourism dynamics. By linking growth rates to quantifiable indicators from the WHO International Health Regulations core capacity index, which evaluates adherence to global health standards, the model effectively illustrates tourist population behaviours alongside health capacity. It highlights trends of decline or rejuvenation during the poststagnation phase and provides predictive insights relevant to five representative countries.
Keywords: 330; Index-dependent growth rate; Periodic solutions; Poststagnation stage; Tourism area life cycle